Neural Hyperactivity Is a Core Pathophysiological Change Induced by Deletion of a High Autism Risk Gene Ash1L in the Mouse Brain - Gao, Yuen; Aljazi, Mohammad B.; He, Jin (Frontiers in Behavioral Neuroscience, 2022)
ASH1L is one of the highest risk genes associated with autism spectrum disorder (ASD) and intellectual disability (ID). Our recent studies demonstrate that loss of Ash1l in the mouse brain is sufficient to induce ASD/ID-like behavioral and cognitive deficits, suggesting that disruptive ASH1L mutations are likely to have a positive correlation with ASD/ID genesis. However, the core pathophysiological changes in the Ash1l-deficient brain remain largely unknown. Here we show that loss of Ash1l in the mouse brain causes locomotor hyperactivity, high metabolic activity, and hyperactivity-related disturbed sleeps and lipid metabolic changes. In addition, the mutant mice display lower thresholds for the convulsant reagent-induced epilepsy and increased neuronal activities in multiple brain regions. Thus, our current study reveals that neural hyperactivity is a core pathophysiological change in the Ash1l-deficient mouse brain, which may function as a brain-level mechanism leading to the Ash1l-deletion-induced brain functional abnormalities and autistic-like behavioral deficits.